2013 IEEE 13th International Conference on Rehabilitation Robotics (ICORR) 2013
DOI: 10.1109/icorr.2013.6650368
|View full text |Cite
|
Sign up to set email alerts
|

An inverse dynamic analysis on the influence of upper limb gravity compensation during reaching

Abstract: Muscular dystrophies (MDs) are characterized by progressive muscle wasting and weakness. Several studies have been conducted to investigate the influence of arm supports in an attempt to restore arm function. Lowering the load allows the user to employ the residual muscle force for movement as well as for posture stabilization. In this pilot study three conditions were investigated during a reaching task performed by three healthy subjects and three MD subjects: a control condition involving reaching; a simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Investigating the involvement of rotator cuff muscles and deeper muscles such as the serratus anterior would require more invasive techniques such as fluoroscopy or intramuscular needle electromyography. As part of a complementary approach to understanding rotator cuff muscle contributions, biomechanical musculoskeletal models 21,36,37 could also be used. As a long-term research perspective, it would be interesting to further evaluate whether the use of arm supports would result in more efficient movements that require less effort and would therefore enable the performance of tasks such as eating for longer periods.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Investigating the involvement of rotator cuff muscles and deeper muscles such as the serratus anterior would require more invasive techniques such as fluoroscopy or intramuscular needle electromyography. As part of a complementary approach to understanding rotator cuff muscle contributions, biomechanical musculoskeletal models 21,36,37 could also be used. As a long-term research perspective, it would be interesting to further evaluate whether the use of arm supports would result in more efficient movements that require less effort and would therefore enable the performance of tasks such as eating for longer periods.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Two articles were added after reference cross cheques. Finally, eight articles were included for reviewing after the inclusion process [18][19][20][21][22][23][24][25] ( Table 1). Two studies, ongoing until 31 December 2020 and 2019, respectively, were identified from the goverenment clinical trial source [26,27] (Table 2).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The evaluated DAS were a prototype A-gear [19,28], and commercially available devices Armon Ayura [26,27,29], Armon Edero [25,29], Gowing [24,30], JAECO MultiLink Arm with Elevation Assist [25,31], JAECO WREX [21,23,26,27,31], SLING [20,22,30], and Top-Help [22,30], and a JAECO WREX modified with a trunk support prototype [18] (Table 1). These DAS provide gravity compensation through adjustable counter-weights (SLING) or springs (A-gear, Armon Edero, JAECO MultiLink Arm with Elevation Assist, JAECO WREX, Top-Help) with an additional actuator that adjusts the springs' tension (Armon Ayura, Gowing).…”
Section: Dynamic Arm Support Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, we constructed a low-inertia, large workspace sling support [35], [36]. We suspended an arm rest from the ceiling using 165 cm of high-strength nylon rope.…”
Section: B Ceiling Support -Positive Controlmentioning
confidence: 99%